Health services utilization and the factors that influence on the utilization - Erdem, Ramazan; Pirinçci, Edibe (My University, 2003)
The purpose of this study is to examine of factors that impact on utilization of health services theoretically. This factors are expressed in three groups. Those are predisposing, enabling and needs factors. The predisposing factors includes demographic, socio-economic, attitude and behavioral factors. In the enabling factors, there are family and governmental factors. And needs factors explain perceived and evaluated need. In addition to this, the studies about utilization of health services are examined. According to the results of these studies, age, gender, marital status, income level, education, health insurance coverage, resident, etc. effect the utilization of health services.
Sa?lik hizmetlerinde kullanim ve kullanimi etkileyen faktörler
Keywords: Attitude and behavior; Health services; Utilization